Penegakan Hukum pada Pelaku Tindak Pidana Penganiayaan Anak di Bawah Umur di Kabupaten Kudus - Subakti, Muhammad Alfin; Sunardi, Sunardi; Azizah, Naili (Universitas Syiah Kuala, 2025)
This research uses an empirical juridical method, combining normative studies of laws and regulations with the realities of practice in the field. The research location was the Kudus District Court and the Kudus Women and Children Protection Network (JPPA). Data were collected through interviews, document studies, and observations of child abuse cases. The results indicate that child abuse crimes in Kudus range from minor to serious, and even resulting in death. Law enforcement is carried out through the juvenile criminal justice process, while adhering to the principles of child protection. However, its implementation still faces obstacles such as limited facilities, low public legal awareness, a permissive culture of violence, and suboptimal law enforcement officers. Efforts to strengthen child protection include improving coordination between law enforcement agencies, expanding the role of the community, and prioritizing restorative justice to safeguard children's interests. This research is expected to contribute theoretically to the development of juvenile criminal law and provide practical recommendations for improving the effectiveness of legal protection in Kudus Regency.